An experimental investigation on partial-ductile mode grinding of silicon - Konneh, M. (2002)
This research work was primarily concentrated on precise ductile-mode grinding (milling) of flat surfaces of silicon, mainly Integrated Circuit (IC) silicon chips (dies), which were about 700 Âµm thick and the top of their surfaces covered with a silicon nitride layer. Substantial amount of partial-ductile streaks on a machined silicon surface shortens polishing time dramatically. This is of vital importance particularly in chip-making and optical industries for failure analysis. Failure analysis is a technique usually practised for locating a fault in a finished IC product. In chip-making industries, the analysis is done on the damage-free mirror-like finished silicon die of the IC. Grinding, lapping and/or polishing operations are required to get such a smooth surface. Precision grinding in a ductile mode therefore remains the critical and most important machining operation as the surface and sub-surface damages will be minimized. This results in good quality surface in terms of surface finish and flatness and at the same time generating the maximum amount of ductile streaks on the machined surface. Silicon material other than the IC silicon was also tried out for purpose of comparison and because of limited number of IC chips. Silicon like any hard and brittle material is well known for its low machinability unless it is machined under ductile mode condition. Ductile mode machining is a process that makes brittle materials to behave like ductile materials. A low cost machining technique, which facilitates partial-ductile mode grinding of small areas on thin wafer-like silicon, was developed. A specially modified conventional MAHO CNC Vertical Milling Centre that has an air driven low powered high-speed attachment (precision jig grinder) facilitated the diamond grinding. Special fixtures were designed and fabricated that held the workpieces in position and prevented them from damage during machining. Both traditional and statistical techniques for designing of experiments and subsequent analysis of results were employed in this study. A low cutting force dynamometer (Compacdyn) was used to measure cutting forces. Form Talysurf and Surfcom Surface Analysers and Atomic Force Microscope were used to measure surface texture parameters. Optical, Scanning Electron microscopy techniques, together with the Surfcom Surface Analyser and Atomic Force Microscope, were used to examine the surface morphology of the machined silicon surfaces. It was found that the amount of ductile streaks generated on a work-piece surface was not only dependent on feed and depth of cut but also on the grit size of diamond abrasive. The machining technique of grinding yielded ground surfaces with Ra as low as 50 nm, and forces around 0.8 Newton. Flatness of the machined surfaces is very good. A model of surface roughness (Ra) for precision grinding of thin silicon has been established.